Literasi Budaya Dan Kewargaan Sebagai Upaya Mempertahankan Kebudayaan Di Tengah Kemajemukan Masyarakat Indonesia - Asti Widiastuti; Farina Trias Alwasi; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Indonesia is a country with a diverse society, namely having various ethnic groups, languages, customs, customs, beliefs and social layers. With this diversity, Indonesia is rich in culture, but currently culture in Indonesia is starting to fade due to the lack of insight and understanding of the people around the culture. Lack of cultural literacy and citizenship is one of the reasons why national culture is gradually disappearing in social life. Thus, through cultural and civic literacy, people are expected to have knowledge about history, contributions and perspectives about culture as well as be able to apply it and understand and have a positive attitude towards Indonesian culture as a national identity amidst the diversity of Indonesian society.